Atomically Dispersed Copper on N‐Doped Carbon Nanosheets for Electrocatalytic Synthesis of Carbamates from CO2 as a C1 Source. Issue 9 (22nd March 2021) - Li, Shi‐Ming; Shi, Yi; Zhang, Jing‐Jie; Wang, Ying; Wang, Huan; Lu, Jia‐Xing
Abstract: The synthesis of carbamates by electrocatalytic reduction of CO2 is an effective method to realize the utilization of CO2 resources. The development of high‐performance electrocatalysts to complete this process more efficiently is of great significance to sustainable development. Owing to their unique structural characteristics, single‐atom catalysts are expected to promote the reaction process more efficiently. In this study, an atomically dispersed Cu species on N‐doped carbon nanosheet composite material (Cu−N−C) was prepared by metal‐organic framework derivatization. Compared with traditional Cu bulk electrodes, the Cu−N−C material has better catalytic performance for the synthesis of methyl N ‐phenylcarbamate; and the optimized yield reached 71 % at room temperature and normal pressure. The Cu−N−C material has good stability that the catalytic performance does not decrease after repeated use for 10 times. In addition, the Cu−N−C material has good applicability to this catalytic system, and a variety of amines can be smoothly converted into corresponding carbamates. Abstract : SAC magique ! An atomically dispersed Cu species on N‐doped carbon nanosheet composite material (Cu−N−C) is prepared by using MOF derivatization for the electrocatalytic synthesis of carbamates using CO2 . Compared with traditional Cu bulk electrodes, Cu−N−C has better catalytic performance. In addition, Cu−N−C has good stability and is generally applicable for a variety of amines.